1998
DOI: 10.1097/00004714-199804000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Nefazodone in Major Depression

Abstract: One hundred sixty-six patients suffering from major depressive disorders were treated for 8 weeks with nefazodone in an open study in dosage ranges from 200 to 600 mg. This report focuses primarily on the first week of therapy and on the concomitant use of several benzodiazepines, one of which is not metabolized by the cytochrome system (temazepam). Triazolam response was further evaluated as a function of two nefazodone dosage regimens provided during the first week of therapy, one group receiving nefazodone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…These patients often continue to take their BZ for years, at least in part to avoid withdrawal symptoms. Previously published studies have found clinically significant levels of anxious and depressive symptomatology in these patients (Rickels et al 1990) despite seemingly adequate BZ dosing. This implies that some patients may be bound to a treatment that only partly relieves their symptoms.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These patients often continue to take their BZ for years, at least in part to avoid withdrawal symptoms. Previously published studies have found clinically significant levels of anxious and depressive symptomatology in these patients (Rickels et al 1990) despite seemingly adequate BZ dosing. This implies that some patients may be bound to a treatment that only partly relieves their symptoms.…”
Section: Introductionmentioning
confidence: 75%
“…There is significant variability among patients, however, in the severity of the BZ withdrawal syndrome as well as the ability to maintain a BZ-free state after discontinuation. Previous research by this group and others (Tyrer et al 1983 ;Rickels et al 1990 ;Schweizer et al 1990) has demonstrated that gradual, as opposed to abrupt, taper of BZ medications is better tolerated and results in a significantly higher success rate for discontinuation. Yet even with gradual taper, there remains a group of patients that are unable to tolerate BZ discontinuation.…”
Section: Introductionmentioning
confidence: 86%
“…'relapse' or 'rebound anxiety '), although the presence of certain withdrawal-specific anxiety symptoms (e.g. perceptual distortions, de-realization, nausea) (Schopf, 1983 ;Tyrer et al 1983 ;Busto et al 1986) and a characteristic time course of onset and offset (Busto et al 1986;Rickels et al 1990), may sometimes help. Nonetheless, no scale used to measure BZ discontinuation symptom severity can entirely overcome this confounding of withdrawal and re-emergent anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The significant variability among patients in the severity of withdrawal has been associated with both drug treatment and patient factors. Drug treatment factors found to be important have included BZ dose (Rickels et al 1988), potency (Tyrer, 1988) and half-life (Fontaine et al 1984 ;Rickels et al 1986;Roy-Byrne et al 1989), duration of treatment (Rickels et al 1983) and rate or speed of taper/discontinuation (Roy-Byrne et al 1989 ;Rickels et al 1990 ;Schweizer et al 1990). Patient factors have included type of diagnosis (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation